Three Concepts That Are Confused With Each Other In Academia: Alevism, Bektashism, and Shiism - Topuz, Birol (Journal of Alevism-Bektashism Studies, 2023)
When Islamic history is analyzed, it is seen that the concept of “Shia” is one of the most striking concepts. However, it is also known that this concept is wrongly used in the same way as Alevism and Bektashism by many people and even many researchers. In this study, all these three concepts will be analyzed in all aspects. And the similarities and differences between them will be tried to be explained in a more understandable way. What are the similarities and differences between Alevism, Bektashism and Shiism in terms of belief, practice, sources and culture? Are these three groups the same with each other or not? If they have differences, what are these differences? The answers to all these questions, which exist the main questions of the study, will be given in a simple graphic at the end of the study. The methodology of this study will be a comparative, thematic and holistic approach to the main sources and studies.
Keywords: Alevism; Bektashism; Shiism